2021
DOI: 10.26508/lsa.202101191
|View full text |Cite
|
Sign up to set email alerts
|

ADAR1 RNA editing regulates endothelial cell functions via the MDA-5 RNA sensing signaling pathway

Abstract: The RNA-sensing signaling pathway has been well studied as an essential antiviral mechanism of innate immunity. However, its role in non-infected cells is yet to be thoroughly characterized. Here, we demonstrated that the RNA sensing signaling pathway also reacts to the endogenous cellular RNAs in endothelial cells (ECs), and this reaction is regulated by the RNA-editing enzyme ADAR1. Cellular RNA sequencing analysis showed that EC RNAs endure extensive RNA editing, especially in the RNA transcripts of short i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 56 publications
3
8
0
Order By: Relevance
“…In line with other reports ( Liddicoat et al, 2015 ; Guo et al, 2021 , 2022a ), our RNA-seq data also showed that the dsRNA sensors MDA5 ( IFIH1 gene) and retinoic acid-inducible gene I (RIG-I; DDX58 gene) were increased and borderline increased (FDR = 0.11), respectively, following ADAR1 knockdown ( Figure 1C ). Increases in these transcripts translated to modestly but not significantly elevated protein levels ( Figures 2A , E ) that tended to correlate with downstream products of MDA5/RIG-I signaling ( p = 0.02–0.09, Supplementary Figure S3B ).…”
Section: Resultssupporting
confidence: 92%
“…In line with other reports ( Liddicoat et al, 2015 ; Guo et al, 2021 , 2022a ), our RNA-seq data also showed that the dsRNA sensors MDA5 ( IFIH1 gene) and retinoic acid-inducible gene I (RIG-I; DDX58 gene) were increased and borderline increased (FDR = 0.11), respectively, following ADAR1 knockdown ( Figure 1C ). Increases in these transcripts translated to modestly but not significantly elevated protein levels ( Figures 2A , E ) that tended to correlate with downstream products of MDA5/RIG-I signaling ( p = 0.02–0.09, Supplementary Figure S3B ).…”
Section: Resultssupporting
confidence: 92%
“…MDA-5 has been shown to be required for IFN pathway activation in ADAR1-deficient mouse models [ 20 24 , 28 , 29 ] and deletion of MDA-5 completely rescues the lethality in catalytic null Adar1 E861A/E861A mutant mice [ 18 , 28 ]. However, the postnatal lethality of Adar1 ∆7–9 [ 19 ], Adar1 ∆2–13 [ 30 ], Adar1 ∆12–15 [ 31 ], and P150 −/− [ 19 ] could not be rescued by either MDA-5 or MAVS deletion. Whether the phenotype observed in ADAR D1113H mutant mice is MDA-5-dependent was yet to be determined.…”
Section: Deletion Of Mda-5 Prevents Isg Expression Astrocytosis and G...mentioning
confidence: 99%
“…Because NK2 homeobox 5 ( Nkx2-5 ) gene is also expressed in other cell type (i.e., endothelium) and tissue types (tongue, thymus, and spleen) during embryonic development ( 51 ), it is possible that the ablation of Adar1 in early cardiac field may not be specific for cardiomyocytes. However, another recent study crossing Adar1 conditional knockout mice with the endothelial-specific cre driver, VE-Cadherin-Cre (Chd5-Cre), demonstrated that the ablating Adar1 in endothelial cells did not result in embryonic death, instead postnatal death due to growth retardation within three weeks after birth for 75% of neonates ( 52 ). To further confirm the important role of Adar1 in cardiomyocytes, another study crossing Adar1 conditional knockout mice with the tamoxifen-inducible cardiomyocyte specific cre-driver, αMHC-MCM, showed that ablating Adar1 in adult cardiomyocytes resulted in increased lethality due to increased endoplasmic stress leading to apoptosis and reduction in miRNA levels, especially miR-199a-5p that regulates unfolded protein response (UPR) ( 33 ).…”
Section: A-to-i Rna Editingmentioning
confidence: 99%